(untitled) (Cardiovascular Journal, 2017)
Background: In search of factors influencing the postoperative health-related quality of life after heart valve replacement, the present study was designed to see the effects of valve replacement on the long-term healthy survival. The aim of the study was to explore whether the Preoperative variables, such as clinical characteristics and test data could he used to predict the effects of valve replacement on functional status and quality of life in patients with heart valve malfunctions after alter surgical intervention. Method: We retrospectively identified 200 patients who underwent heart valve replacement for stenosis between 2005 and 20l2 in the department of Cardiac Surgery. BSMMU. Dhaka. Bangladesh and survived the surgery and initial 30 day postoperative period. Late follow-up between January 2013 and July 2015 was done and completed in 50% cases. Results: Among 100 study population, 47 were male and the rest 53 were female, aged 22 to 65 years (mean 37.0±7.4 years). The quality of life was assessed with the Medical Outcomes Study Short Form -36 (MOS SF-36) and the functional outcome was evaluated using New York Heart Association (NYHA) functional class scores, in addition to analysis of laboratory tests, like ECG, X-ray chest, echocardiography, prothrombin time. Evaluation of preoperative medical history revealed that there were hypertension in 7l%, diabetes mellitus in l3%, and history of stroke in 09% patients. Prolonged length of stay in intensive care unit and in hospital (mean: 14.7 and 37.l days respectively) was observed in 17% patients. Late postoperative survival rate was 86% at l year and 63% at the end of 5 years. Predictors of late morbidity and mortality were Preoperative or Perioperative complications, preoperative history of stroke, chronic obstructive pulmonary disease. postoperative renal dysfunction. The mean NYHA functional class for all late survivors improved from 3.6 ± 0.9 to 1.9 ± 0.7. Late survival was worse for those who were in an advanced NYHA functional class before surgery. Patient in NYHA Functional class Ill and IV had a worse late survival late than those in Class I or ll. There was Significant improvement in all 8 health domains of the SF-36 Questionnaire in the overall sample. Conclusion: The present study indicated that the late survival rate and functional outcome after heart valve replacement in Bangladeshi population with major valvular dysfunction was satisfactory. It was also observed that the preoperative physical as well as mental health status were identified as the only risk factors for potential non-improving quality of healthy survival following heart valve replacement after correction for age, gender and type after surgery. Cardiovasc. j. 2017; 10(1): 21-30